The relationship between hotel image, customer satisfaction and customer loyalty: a case study in Labuan, Malaysia - Stephen L. Sondoh Jr; Geoffrey H. Tanakinjal; Yapp, Emily, Hon Tshin; Judy Jolonius (2012)
The primary objective of this study is to examine the relationships between hotel image, customer satisfaction and loyalty of the selected hotels in Labuan. The study also examines the mediating effect of customer satisfaction on the relationship between hotel image and customer loyalty. Data from 210 hotel’s customers were used for the statistical analysis. The multiple regression analysis results show that all of the dimensions of hotel image attributes have a significant effect on customer satisfaction. However, only one dimension of hotel image i.e. contact personal was found to have no significant influence on customer loyalty. The results also indicate that customer satisfaction does influence customer loyalty. The results from hierarchical regression show that customer satisfaction does mediate the relationship between hotel image attributes and customer loyalty. Managerial implication, limitations of the study and recommendations for future researchers are also included in the study.